Pattern of Childhood Cholelithiasis- Experience in a Tertiary Level Hospital (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Cholelithiasis is being frequently diagnosed in children, although not as often as in adult. The real aetiology of gallstone formation is poorly understood, but some inciting factors are assumed to be involved in gallstone formation in children. Traditionally cholelithiasis in children is classified as haemolytic or nonhaemolytic in origin. Nonhaemolytic cholelithiasis seems to be more frequent than haemolytic cholelithiasis at present.Aim: To find out the pattern of childhood cholelithiasis presenting in a tertiary level military hospital.Methods: This retrospective observational study was carried out in the Department of Paediatric Surgery, CMH Dhaka from January 2015 to December 2018. A total of 35 children with cholelithiasis were admitted in this hospital.Results: During the study period 35 children with cholelithiasis were admitted. Among them maximum children 31(88.6%) were in the age group of 6-12 years. Out of them 23(65.7%) were female and 12(34.3%) were male making a female to male ratio of 1.92:1. Twelve children (34.3%) were asymptomatic and 23(65.71%) were symptomatic. Among symptomatic group 10(28.6%) had biliary colic, 10(28.6%) had nonspecific abdominal pain and 3(13.0%) had acute abdominal pain. Out of these 35 children, only 4(11.4%) had link with haemolytic anaemia.Conclusion: Cholelithiasis in children is being recognized with increased frequency in recent years. The ratio of cholecystitis and cholelithiasis varies considerably in different countries and centres. Childhood cholelithiasis has less chance of complication and high rate of resolution.JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 8-11